Yam bean, Pachyrhizus DC. - Sørensen, M.; Leibniz Institute of Plant Genetics and Crop Plant Research (1996)
For P. erosus, P. ahipa and P. tuberosus, descriptions are given of the taxonomy, botany, morphology, ecology, reproductive biology, agronomy, N fixation, chemical composition, nutritive value, uses, origin of the cultivated species (with descriptions of the wild species P. ferrugineus and P. panamensis) and geographical distribution, genetic resources and breeding, and future prospects. (Abstract © CAB ABSTRACTS, CAB International)